Association between breast cancer risk factors and molecular type in postmenopausal patients with hormone receptor-positive early breast cancer - Wunderle, Marius Thorsten; Pretscher, Jutta; Brucker, Sara Y.; Volz, Bernhard; Hartmann, Arndt; Fiessler, Cornelia; Hein, Alexander; Häberle, Lothar; Jud, Sebastian M.; Lux, Michael P.; Janni, Wolfgang; Loehberg, Christian R.; et al. (Breast cancer research and treatment, 2019)
Breast cancer, molecular subtype, risk factors, hormone replacement therapy, prognosis